2022
DOI: 10.3390/polym14122345
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Roller Rotation Pattern in the Spreading Process of Polymer/Short-Fiber Composite Powder in Selective Laser Sintering

Abstract: In this study, for the first time, a forward-rotating roller is proposed for the spreading of CF/PA12 composite powder in the selective laser sintering (SLS) process. The mesoscopic kinetic mechanism of composite particle spreading is investigated by utilizing the “multi-spherical” element within the discrete element method (DEM). The commercial software EDEM and the open-source DEM particle simulation code LIGGGHTS-PUBLIC are used for the simulations in this work. It is found that the forward-rotating roller … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Chen et al examined the effect of fiber particles and found that increasing the fiber length reduces the spreadability of mixed powders and decreases the packing density [19], and they proposed a deposition mechanism and percolation effect of bimodal powder particles [20]. Cheng et al [21] and Si et al [22] examined the effect of different operation factors and mechanisms of spherical polymers. However, the investigation of non-spherical polymer particles is rather rare compared to those of spherical particles.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al examined the effect of fiber particles and found that increasing the fiber length reduces the spreadability of mixed powders and decreases the packing density [19], and they proposed a deposition mechanism and percolation effect of bimodal powder particles [20]. Cheng et al [21] and Si et al [22] examined the effect of different operation factors and mechanisms of spherical polymers. However, the investigation of non-spherical polymer particles is rather rare compared to those of spherical particles.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, it is discretized into interacting particle ensembles (two-dimensional disk (2D) and three-dimensional sphere (3D) are the main particle shape in space) by constructing particle ensembles into specimens of different geometries, utilizing a contact model forming interactions and iterative analysis based on Newton’s second law to make the macroscopic mechanical properties of the numerical specimen approach those of real materials [ 25 ]. Therefore, with the DEM method, the problems of discontinuities, high gradient variables, and remeshing in fracture or damage can be overcome [ 26 , 27 , 28 , 29 ]. The DEM method has been widely used to describe the macroscopic mechanical properties of materials, such as rock [ 30 , 31 ], soil [ 32 ], and concrete [ 33 ].…”
Section: Introductionmentioning
confidence: 99%